2009
DOI: 10.1007/s10452-009-9254-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of microbial eukaryotic community composition in the large, shallow, subtropical Taihu Lake, China

Abstract: Microbial eukaryotic community (0.8-20 lm) composition and its seasonal variation were investigated in large, shallow, subtropical Lake Taihu located in Southeast China. The water samples were collected monthly from August 2006 to July 2007 at two sites distantly located in Meiliang Bay and Lake Center, which differed strongly in their trophic status and sediment resuspension. The microbial eukaryotic community compositions (MECC) were measured using denaturing gradient gel electrophoresis (DGGE) of PCR-amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
2
13
1
Order By: Relevance
“…Our results suggesting a structuring impact linked to trophic level and depth are consistent with the recent conclusions reported by Chen et al (2009). It appears here a specificity of small eukaryote structure in the eutrophic lake and in the deepest zones close to the sediments.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Our results suggesting a structuring impact linked to trophic level and depth are consistent with the recent conclusions reported by Chen et al (2009). It appears here a specificity of small eukaryote structure in the eutrophic lake and in the deepest zones close to the sediments.…”
supporting
confidence: 93%
“…However, using FISH (CHLO02 probe), Mangot et al (2009) showed during a 1-year study that Chlorophyta were well represented, accounting for 17.9% of small eukaryotes in Lake Bourget. Similarly, Chen et al (2009) observed, by morphological observations, that some pigmented taxa, such as Tetraedron sp., were abundant in the Meiliang Bay, but were not detected by molecular analysis. All these data suggest that 18S rRNA gene-based studies may underestimate pigmented cells in samples, and because of their limitations, molecular approaches based on PCR may not reflect the real diversity.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…This method provides the possibility to identify the community members by reamplifying and sequencing of the excised bands. Previously, DGGE technique was successfully applied to reveal the alterations of bacterial or total microbial communities in freshwater and seawater habitats infl uenced by different environmental factors [10,11,12,13,14]. According to the UPGMA dendrogram based on the DGGE patterns, signifi cant seasonal changes with less spatial differences were found among the total planktonic bacterial communities of Lake Hévíz (Fig.…”
Section: Microbial Community Structuresmentioning
confidence: 99%
“…Some of these bacteria were revealed mainly from still water (lakes, ponds, reservoirs), e.g. Aquiluna rubra, Rheinheimera aquatica, Polynucleobacter cosmopolitanus, Polynucleobacter acidiphobus from which 'Candidatus Aquiluna rubra' and both Polynucleobacter species are typical planktonic freshwater microbes [14,17,18,19]. Others, e.g.…”
Section: Acta Microbiologica Et Immunologica Hungarica 63 2016mentioning
confidence: 99%